Ureteric carcinoma - Stephen A. Geller; Fernando Peixoto Ferraz de Campos (University of São Paulo, 2014)
Ureteric neoplasms are rare tumors. The annual incidence (during the period 1995-2005) was 0,95-1,15/100.000 person-year. They are almost always urothelial tumors, especially papillary transitional cell carcinoma, as in the image above, and are less common than tumors of the renal pelvis and 10 times less common than urinary bladder tumors. In a large series of 1249 cases of urothelial neoplasms of the upper urinary tract (pelvis and ureter) (upper urinary tract tumors; UUTT) 34% of the cases involved the ureter, and in 8% the neoplasia was found in both sites concomitantly. Concomitance with bladder tumors is also observed, either synchronously or methachronously. When metachronous; bladder tumors precede UUTT in 10,2% of cases, and when synchronous in 49%.